1971
DOI: 10.1083/jcb.51.1.116
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ETHIDIUM BROMIDE ON MITOCHONDRIAL DNA SYNTHESIS AND MITOCHONDRIAL DNA STRUCTURE IN HELA CELLS

Abstract: The synthesis of mitochondrial DNA (mDNA) in HeLa cells is selectively inhibited by relatively low concentrations of ethidium bromide . After exposure of cells to strongly inhibitory concentrations of the drug, the apparent superhelix density of mDNA is rapidly increased, as judged by its buoyant density in CsC1 in the presence of ethidium bromide . Mitochondrial DNA synthesized in the presence of partially inhibitory concentrations of ethidium bromide is also altered in its buoyant density in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…Therefore, we also depleted mitochondrial DNA from WT macrophages using ethidium bromide. In agreement with previous reports (39,40), ethidium bromide treatment inhibited mitochondrial (Cox2) but not nuclear encoded DNA (Cs, Bhad) (Supplemental Figure 4B), reducing the expression of complex I, complex II, and complex IV by approximately 40% (Supplemental Figure 4C). Consistent with findings from β1 -/-macrophages, we found that lower levels of mitochondria led to reductions in fatty acid oxidation ( Figure 3C) and dramatically increased the phosphorylation of JNK ( Figure 3D).…”
Section: Figuresupporting
confidence: 80%
“…Therefore, we also depleted mitochondrial DNA from WT macrophages using ethidium bromide. In agreement with previous reports (39,40), ethidium bromide treatment inhibited mitochondrial (Cox2) but not nuclear encoded DNA (Cs, Bhad) (Supplemental Figure 4B), reducing the expression of complex I, complex II, and complex IV by approximately 40% (Supplemental Figure 4C). Consistent with findings from β1 -/-macrophages, we found that lower levels of mitochondria led to reductions in fatty acid oxidation ( Figure 3C) and dramatically increased the phosphorylation of JNK ( Figure 3D).…”
Section: Figuresupporting
confidence: 80%
“…The column was washed with the same buffer until no more protein was eluted and then eluted with 5 column volumes of 25% formamide in 10 mM Tris-hydrochloride, pH 7.4, followed by 5 with an equal volume of complete Freund adjuvant, and 0.5 ml corresponding to material from 20 10-cm tissue culture dishes was injected intraperitoneally per BALB/c mouse. A similar booster injection in incomplete Freund adjuvant was given on day 14, and the mice were hyperimmunized by an intravenous injection of the same antigen in PBS on day 28. Mice were sacrificed 3 or 4 days later, the spleens were removed, and the lymphocytes were fused with SP2/0 myeloma cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were supplemented with penicillin-streptomycin, and used at subconfluent densities. Cells were labeled for 4 h with [35S]methionine at 10 ,uCi/ml in methionine-free medium containing 2% undialyzed fetal calf serum in the presence of actinomycin D (0.04 ,ug/ml) and ethidium bromide (1.5 ,ug/ml) added 30 min before addition of the label to suppress ribosomal (9,40,54) and mitochondrial (28,58) RNA and protein synthesis, respectively. Cell culture materials were from GIBCO Laboratories, and radiochemical reagents were obtained from New England Nuclear Corp.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria and mtDNA are believed to be closely associated with cell growth, because mitochondria are organelles that produce chemical energy in the form of ATP (Kotsifas et al, 2003;Zhu et al, 1997). Ethidium bromide (EtBr) is known to be a potent inhibitor of mtDNA replication and transcription in mammalian cultured cells (Nass, 1970;Leibowitz, 1971;Zylber et al, 1969) and avian cultured cells (Desjardins et al, 1985;Desjardins et al, 1989), but it does not substantially affect the synthesis of nuclear DNA (Radask et al, 1971;Nass, 1972;LeblondLarouche et al, 1979). In cultures of Dictyostelium Ax-3 cells, EtBr actually inhibits any new synthesis of mtDNA (Firtel and Bonner, 1972;Kobilinsky and Beattie, 1977), and growth of Ax-3 cells stops after one or two generations in the presence of 10 µg/ml EtBr (Stuchell et al, 1973).…”
mentioning
confidence: 99%